(3GdJShjb (B:s (3GdSdY h GdCSYGQ GdLRA GdQGHY (B/s - (3faGY, eGRfs ((3OeTb (B:s (3OGQ YdGA GdOjf ,s, 2007)
(3jjJfGhd gPG GdLRA ef cJGH GdJShjb GdYfUQ GdChd ef GdeLehYI GdJShjbjI hgh (S0(3GdSdYI(S1 (3ef LhGfHgG cGaI, hdGSjeG ef MjK JdHjI eJWdHGJ GdeSJgdcjf, hGdeTcdGJ GdJj bO JXgQ YfO GJNGP GdbQGQGJ GdeJYdbI HGdSdYI PGJgG, hGdYhGFb GdJj Ydi GdeShbjf GdJZdH YdjgG Ydi VhA GdJZjjQ GdSQjY GdPj gh EMOi Cge SeGJ GdCShGb GdeYGUQI hGdPj jaQV Ydi GdefJLjf EfJGL hWQM SdY LOjOI HTcd OGFe JhGcH gPG GdJZjjQ(B. (3ceG jaQV Ydi eOjQj GdJShjb Cf jOjQhG HOqbI YedjGJ GdHjY CKfGA GdOhQI GdMjGJjI ddSdYI(B. (3hjcQS gPG GdcJGH aUdkG ddSdY ZjQ GdeGOjI CdG hgj GdNOeGJ hGdehGUaGJ GdaQjOI, hCSGdjH Jcjja WQb gPg GdNOeGJs
Keywords: (3Lhf ShfOQRs; (3ZGQj CQeSJQhfZs; (3ajQhfjcG HhfZs; (3JShjbs